Splicing factor proline/glutamine-rich is a novel autoantigen of dermatomyositis and associated with anti-melanoma differentiation-associated gene 5 antibody. (February 2017) - Hosono, Yuji; Nakashima, Ran; Serada, Satoshi; Murakami, Kosaku; Imura, Yoshitaka; Yoshifuji, Hajime; Ohmura, Koichiro; Naka, Tetsuji; Mimori, Tsuneyo
Abstract: Objective: Anti-MDA5 antibody positive dermatomyositis (DM) and clinically amyopathic DM (CADM) often develop into rapidly progressive interstitial lung disease, but their pathogenesis remains unclear. We observed that sera from DM/CADM patients immunoprecipitated a common 110 kDa polypeptide. We investigated this autoantigen and its clinical significance. Methods: Autoantibodies were screened in 333 patients with various connective tissue diseases (CTDs) and 20 healthy controls (HCs) by immunoprecipitation with [ 35 S]methionine-labeled HeLa cells. Immunoabsorbent column chromatography was used to purify the reactive autoantigen which was subsequently analyzed by peptide mass fingerprinting. Results: Anti-110 kDa antibody was detected in sera from 27 DM/CADM patients, but not in sera from other CTD patients or HCs. All patients with anti-110 kDa antibody had anti-MDA5 antibody. The maximum KL-6 levels in anti-110 kDa antibody-positive patients were higher than in anti-110 kDa antibody-negative patients, and all anti-MDA5-antibody-positive patients who showed the recurrence of DM/CADM were anti-110 kDa antibody-positive. The corresponding autoantigen was identified as splicing factor proline/glutamine-rich protein (SFPQ). In some cases, anti-SFPQ antibody was detected at diagnosis (early-detected group), but in other cases, it appeared during the disease course (delayed-detected group). The diagnosis timing of DM/CADM showed seasonal patterns according to the timing of anti-SFPQ antibody appearance. Specifically, 77% (10/13) of patients were diagnosed between August and October in the early-detected group, while 57% (8/14) of patients were diagnosed between January and March in the delayed-detected group. Conclusions: Some anti-MDA5 antibody-positive patients had an antibody to SFPQ, which is known to play a role in innate immune responses. Anti-SFPQ antibody may be involved in the chronic disease course of DM/CADM. The diagnosis timing of DM/CADM in anti-MDA5 antibody-positive patients showed seasonal patterns according to the timing of anti-SFPQ antibody appearance. These findings may provide new insights into the pathogenesis of DM/CADM. Highlights: SFPQ is a novel autoantigen for dermatomyositis (DM). All anti-MDA5-positive patients who showed recurrence of DM/CADM had anti-SFPQ. Diagnosis timing had seasonality according to the timing of anti-SFPQ appearance.